Anaemia in pregnancy: a cross sectional study - Bhaware, Gautam Madhavrao; Muneshwar, Sujata Namdeorao; Pundkar, Rutuja Dinkar (International Journal Of Community Medicine And Public Health, 2021)
Background: Aim of the study was to find the factors leading to anemia in pregnancy. The main objective was to study the various sociodemographic factors leading to anemia and to assess the knowledge about anemia among pregnant females. Methods: The present cross sectional study was carried out at urban health centre, to determine the factors leading to anemia in pregnancy. A total of 100 pregnant females were registered. Demographic data was collected by interview method. A pretested and pre designed questionnaire was used for data collection. Hb was estimated using Sahli’s hemoglobinometer and females having haemoglobin less than 11 mg/dl were considered anaemic. Data analysis was done using SPSS software. Results: The overall mean haemoglobin (Hb) was 9.58+2.2g/dl. It was seen that diet, family size, education, social class, gravida and parity are associated with anaemia in pregnancy. Conclusions: After adjusting for all the possible covariates there seems to be significant association between Hb levels and age group, education level, family size, diet, gravida and parity.